The Influence of Religious, Social Environment, and Motivation on Savings Decision - Pratama, Alief Mas; Utami, Sari (Islamic Banking and Finance, 2024)
Sharia aspects have become an important topic that determines people's decisions, including in the financial sector. The aim of this research is to partially determine the influence of religiosity, social environment, and motivation on the decision to save at a sharia bank. This research uses a quantitative approach, the data collection method used is a questionnaire. The population in this study were sharia bank customers in Bone Regency. The number of samples used was 100 samples. The data that has been collected will go through the stages of validity testing, reliability testing, classical assumption testing, and hypothesis testing. Data processing was carried out with the help of SPSS analysis tools. The results of the research show that religiosity has a positive and significant effect on the decision to save in sharia banks with a t value of 7.241 > t table 1.660, the social environment has no effect on the decision to save in sharia banks with a t value of -0.672 < t table 1.660, and motivation has a positive effect and significant for the decision to save in Islamic banks with a t value of 5.643 > t table 1.660.